More Hawk, Less Seagull: The Importance of Community-Led SoTL Research - Eady, Michelle J.; Rifenburg, J. Michael (Teaching and Learning Inquiry, 2023)
This systematic reflection essay blends research and community engagement with Margaret Kovach’s keynote address at the 2022 conference of the International Society of the Scholarship of Teaching and Learning (ISSOTL) and with the coauthors’ autoethnographic accounts reflecting on their challenges across Australia and the US in conducting ethically responsible SoTL scholarship. The essay is a call for engagement with community-led projects drawing on Neil Drew’s (2006) metaphor of a seagull, who flies in, takes what it wants, and leaves a mess behind. Two stories provided by the co-authors invite further discussion into the hopeful challenges of conducting community-led SoTL research. Click here to read the corresponding ISSOTL blog post.